Effects of N-glycosylation of the human cation channel TRPA1 on agonist-sensitivity. Issue 5 (6th October 2016) - Egan, Timothy J.; Acuña, Mario A.; Zenobi-Wong, Marcy; Zeilhofer, Hanns Ulrich; Urech, David
Abstract : Our experiments confirm N-glycosylation of the human cation channel TRPA1 and suggest a role of the N-glycan at position Asn 747 in determining channel sensitivity to various agonists. Further, the activity-modulating effects of TRPA1 N-glycans are evidently influenced by temperature. Abstract : Determining the functional significance of post-translational modifications advances our understanding of many broadly-expressed proteins, and particularly ion channels. The enzymes that catalyse these modifications are often expressed in a cell-type specific manner, resulting in considerable structural diversity among post-translationally modified proteins that are expressed across a variety of cell types. TRP channels exhibit notably variable behaviour between cell types in vitro and in vivo, and they are frequently modified with N-glycans that contribute to protein function. TRPA1 possesses two putative N-linked glycosylation sites at Asn 747 and Asn 753 that have not yet been studied in detail. In the present study, we show that both of these sites can be modified with an N-glycan and that the glycan at position Asn 747 modulates agonist-sensitivity of TRPA1 in vitro . Additionally, we found that N-glycosylation also modulates cooperative effects of temperature and the agonist cinnamaldehyde (CA) on TRPA1 channel activation. Collectively, these findings suggest a dynamic role played by the N-glycosylation of human TRPA1. They also provide further evidence of the versatility of N-glycans and will assist in efforts to fully understand the complex regulation of TRPA1 activity.